Vývoj metod založených na PCR a jejich aplikace v onkologickém výzkumu a praxi - Hrstka, R; Kolářová, T; Michalova, E; Vojtěšek, B (Klinicka onkologie, 2014)
Since its discovery, PCR has become a conventional method of molecular biology research laboratories and an indispensable tool in diagnostic medicine. Multiple variants of the PCR technique were developed, which enable the analysis of different bio-logical materials at different amounts and reaction conditions. This article briefly summarizes the PCR approaches and points out their applications in oncological research and practice.
Keywords: Neoplasms; biomedicínský výzkum; nádory; lidé; Biomedical Research; polymerázová řetězová reakce; Polymerase Chain Reaction; Humans